Hematemesis melena in a young male patient with suspected of esophageal cancer: a rare case report - Agustini, Made Priska Arya; Pratiwi, Made Sindy Astri; Gotama, Yovita; Sunaka, I Wayan; Wirawan, I Made Suma; Widiasa, Anak Agung Made (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Esophageal cancer (EC) in Indonesia is a rare case. Generally, EC cases occur in people over 50 years of age. In younger patients, it is a rare condition and is usually associated with a poor prognosis. Early-stage EC is generally asymptomatic, so it is often diagnosed late. The most common symptom is dysphagia. Upper gastrointestinal bleeding (UGIB) symptoms in EC are less common and related to emergencies. This study aims to provide an overview of the symptoms and diagnostic approach of EC in young patients. Case presentation: A 19-year-old male patient presented to the emergency department with complaints of black stools and hematemesis. The patient also experienced a weight loss of 8 kg over the past three months. Previously, the patient frequently complained of epigastric pain and heartburn but had never sought medical treatment. Initial laboratory tests revealed severe anemia. An abdominal ultrasound showed multiple nodules in the liver, raising suspicion of metastasis, and endoscopic findings revealed a mass in the distal third of the esophagus. Conclusions: EC should be considered in young patients presenting with warning signs such as UGIB, progressive weight loss, dysphagia, and anemia. A comprehensive history-taking, physical examination and prompt EGD are essential for diagnosing EC.